Professeurs référents : évolution des intentions et logiques d’action au cours d’une formation - Yann Vacher (Recherches en Éducation)
Teacher training has undergone profound reforms wich lead to rethink its contents and methods. The Masters system and the change of structures of the internship year have, as such, produced a revolution in the training practices. The increased use of Referent Teachers (RT) is a significant phenomena. The present article gives the results of a research conducted on the impact of a particular use of this tool during RT training session, teachers who are most of the time appointed on the basis of their expertise in teaching. The research, and the present article, focuses on the effect of training whose objective is to bring the PR in the professionalization process that allows them to overcome this only expertise in teaching. The particular use of Néopass platform that is suggested aims at making RTs aware of the multiplicity of tutoring situation and therefore of the potential profiles of intervention. This article highlights this shift in representation from an expertise in teaching (content) to an expertise on training (méta) but also the necessary conditions to operate this transition to a reflective practice in particular through a structured and perennial training.